The Social Dimensions of Livestock Mobility: Climate Risk, Information Networks, and Resource Governance in Central Senegal - Kitchell, Erin (My University, 2013)
This case study of institutions for information transfer among agropastoralists in Senegal builds on current literature on the human dimensions of climate change, environmental governance, and pastoral mobility. Focusing on information networks can acknowledge the political dynamics of adaptation, in which differential access to and use of information has significant implications. Deeper understandings of changes in forms of information sharing can illuminate how access to information may be linked to control over processes that mediate access to resources. In the case of mobile pastoralism, this requires considering enhanced dissemination of forecasts alongside changing regimes of resource governance. This study examines the impacts of the methods and the breadth of information dissemination on institutions that are central to facilitating pastoral mobility. In addition, it explores interactions between social networks and institutions for resource governance.
Includes Maps, Figures, Appendix and Bibliography.
Keywords: Information Networks; Climate Change; Livestock; Senegal